Investigation of the biogas production potential from algal wastes - Kocer, Anil Tevfik; Ozcimen, Didem (SAGE PUBLICATIONS LTD, 2018)
In recent years, researchers focused their attention on biogas production more than ever to meet the energy demand. Especially, biogas obtained from algal wastes has become a trending research area owing to the high content of volatile solids in algae. The main purpose of this study is to determine the biogas production potential from algal wastes and examine the effect of temperature and particle size parameters on biogas yield. A comparison was made between the biogas production potential of microalgal wastes, obtained after oil extraction, and macroalgal wastes collected from coastal areas. It was found that algal biogas yield is directly proportional to temperature and inversely proportional to particle size. Optimal conditions for biogas production from algal wastes were determined as the temperature of 55 degrees C, a particle size of 200 mu m, a residence time of 30 days and an alga-inoculum ratio of 1:4 (w:w). Highest biogas yield obtained under these conditions was found as 342.59 cm(3) CH4 g(-1) VS with Ulva lactuca. Under thermophilic conditions, both micro- and macroalgal biogas yields were comparable. It can be concluded that algal biomass is a good source for biogas production, although further research is needed to increase biogas yield and quality.
Keywords: Energy; biogas; biomass; algal wastes; Ulva lactuca; oil-extracted Chlorella minutissima; ANAEROBIC CO-DIGESTION; METHANE PRODUCTION; SEWAGE-SLUDGE; ULVA-LACTUCA; MICROALGAE; MACROALGAE; CHLORELLA; PERFORMANCE; CONVERSION; Engineering; Environmental Sciences & Ecology